The meaning of community: the viability of Public Sphere theory and Social Cohesion on social media groups: a reception study of the 'Grahamstown' Facebook Group - Ferreira, Ettioné (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
This study explores the meaning of community to Grahamstown's online social media community, through a case study of the 'Grahamstown' Facebook group (GFG). The study explores the possibilities of social media as a public sphere and the way geographically-based social media sites might contribute to social cohesion in a community. The study explores what kinds of discussions take place on the GFG and why they are happening. It investigates whether these discussions can promote understanding and social solidarity, and whether useful deliberations are taking place, in some kind of approximation of a public sphere. Is this Group contributing to the wellbeing of the community, and how? Drawing on public sphere theory and various conceptions of the concept of social cohesion, the dissertation aims to find out how much of an impact the GFG has on Grahamstown/Makhanda inhabitants' lives and sense of community. The study argues that with the advent of digital media, another 'structural transformation' in Habermasian terms, is underway, both empirically and theoretically. Through more than a dozen in-depth interviews combined with content analysis (via participant observation), the study finds that participation in and exposure to the GFG does lead, for many, to a sense of belonging and social cohesion as community members come together to act in relation to the state, local business and other institutions. The viability of ideas of highly localised (in time and space) 'public sphericules' as an alternative to broader more overarching concepts of a public sphere, is explored in this study. The study also suggests a typology of users, identifying the frequency, tone of voice and motives for participating on the GFG and attempts a periodisation of the GFG's changing role in the community over the past decade.
Keywords: Digital media -- Social aspects; Facebook (Firm); Social participation -- South Africa -- Makhanda; Public sphere -- South Africa -- Makhanda; Group identity -- South Africa -- Makhanda; Grahamstown Facebook Group